More crop per drop – experience in cassava - Sunitha, S; Velmurugan, M; George, James; Sheela, M N (Indian Horticulture, 2019)
Agriculture is probably the main sector where a major share of water is being used and water may become the costliest input in crop production in near future. The situation may become still worse when tuber crops have to compete with high value crops. So there is always a need to find more efficient and judicious ways to use water for irrigation. Microirrigation has gained attention in crop production because of its potential to increase yields and decrease water, fertilizer, and labour requirements if managed properly. It is established that drip irrigation can save almost 40-70% of irrigation water and can result in 30-40% increase in tuber yield of cassava, compared to surface irrigation. Innovative technologies such as suitable water harvesting measures, efficient irrigation methods, water saving techniques etc. are required both under irrigated and rainfed situations, so as to achieve more productive use of water in tuber crop cultivation and to harvest more crop from each drop.